ORCHID SPECIES ANACAMPTIS MORIO AS A POTENTIAL BIOREMEDIATOR OF As, Cd AND Pb - Mikavica, Ivana; Ranđelović, Dragana; Đorđević, Vladan; Gajić, Gordana; Mutić, Jelena (Journal of Applied Engineering Science, 2020)
In this study concentration of toxic elements As, Cd, and Pb were determined in different soil types and belonging orchid species Anacamptis morio vital parts, in order to examine accumulation patterns and provide new insights about the potential use of this orchid in bioremediation technology. The soils developed on limestone, serpentine, and the chert were subjected to the BCR  sequential extraction.  Samples of orchid root and tuber, as underground parts, and stem, leaves, and inflorescence, as above-ground organs, were also analyzed for the content of As, Cd and Pb. During this research, it was observed that metal content in soil is directly proportional to its content in the plant, more specifically in roots, which suggest that A. morio can potentially be used in the phytostabilization of contaminated sites. Values for BCF factors showed Cd immobilization in roots regardless of the soil type. A certain level of arsenic was transferred from root to leaves indicating the potential for accumulation of this element into aboveground organs. Assessment of the phytoremediation potential of this orchid or another plant species from diverse environments is important as it provides information about the possibility of their future application in environmental remediation programs.
Keywords: toxic metals, orchid, bedrock, bioremediation, BCR fractions